Pengaruh Growth Opportunity, Leverage, Firm Size dan Net Working Capital Terhadap Cash Holding - Viki Raodhatul Jannah; Sugeng Priyanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to determine the effect of Growth Opportunity, Leverage, Firm Size and Net Working Capital variables on Cash Holding in Property and Real Estate Sector Companies. The population used in this study is Property and Real Estate Sector Companies listed on the Indonesia Stock Exchange with a research observation period of 2018 – 2022. Sample selection criteria using the purposive sampling method based on predetermined criteria and have been adjusted to the purpose of the research problem, obtained a total of 43 samples from 87 companies. The data analysis technique used in this study Multiple Linear Regression Analysis with SPSS program tool version 21. The results of this study show that Growth Opportunity, Leverage, Firm Size and Net Working Capital have a significant effect on Cash Holding.